ANATOMICAL AND FUNCTIONAL PREREQUISITES FOR THE DEVELOPMENT OF ENDOPROSTHESIS INSTABILITY AFTER MONOCANDYLAR KNEE ARTHROPLASTY - Karpinska, Olena; Khaled Wahbeh, Rami Taleb (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Monocondylar knee arthroplasty allows to restore normal kinematics and function of the knee joint in the case of osteoarthritis limited to the medial or lateral part of the joint. Objective. To identify the patterns and features of secondary anatomical and functional changes in the knee joint after monocandylar arthroplasty depending on the patientʼs gender, weight, etiology of gonarthrosis, the magnitude of the primary joint deformity and bone tissue condition. Methods. The results of the examination of 71 patients (age 37–83 years, follow-up period 3–10 years) were analyzed. In 20 (28.2 %) patients, problems with the arthroplasty joint occurred. joint: increased frontal deformity angle — 8 (40 %), decreased joint mobility — 12 (60 %), pain in the implantation area — 10 (50 %). Results. Preoperative factors that may affect the outcome of monocandylar knee arthroplasty were identified. The main one is reduced bone density, especially localized osteoporosis. In the presence of osteoporotic areas in the area of arthroplasty, the risk of endoprosthesis instability can reach 100 %. The second important factor is frontal deformities of the knee joint of more than 10°. Other factors, such as obesity, meniscal and crossed ligament injuries, fractures of the femoral and tibial condyles, also affect the development of complications, especially with a simultaneous decrease in bone mineral density and/or significant frontal deformity of the knee joint. Conclusions. Monocondylar knee arthroplasty is a reliable, costeffective, low-traumatic method of treating gonarthrosis, but subject to clear indications for its implementation. In the long term, patients with osteoporosis, meniscal and ligamentous injuries, fractures of the condyles, and frontal deformities of more than 10° may develop signs of endoprosthesis instability.